CNN US and CNN Indonesia’s Textual Practice in Framing Humanitarian Narratives: A Critical Discourse Analysis - Dyah Ayu Ratna Jelita; Suhartawan Budianto (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study examines the role of textual practice (micro-structure) in shaping humanitarian narratives in news coverage of the Israel-Palestine conflict by CNN US and CNN Indonesia. Employing Fairclough’s Critical Discourse Analysis (CDA), the research identifies key linguistic features, including lexical choices, sentence structure, modality, rhetorical devices, and pronoun usage, that contribute to the ideological framing of news articles. The findings indicate that CNN US employs neutral and euphemistic language, passive constructions, and hedging devices to maintain journalistic objectivity, whereas CNN Indonesia utilizes emotionally charged language, active voice, and definitive claims to frame the conflict with a strong pro-Palestinian stance. These textual differences underscore the influence of language in constructing public perceptions of humanitarian crises.